Strategi Komunikasi Partisipatif Dalam Perumusan Peraturan Daerah Kota Lubuk Linggau Tentang Penyelenggaraan Pesantren - Ali Fagil Reski Nugroho; Jatmiko Yogopriyatno (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study analyzes participatory communication strategies in the formulation of the Regional Regulation (Perda) concerning the Implementation of Islamic Boarding Schools in Lubuk Linggau City using Riant Nugroho's Participatory Policy Communication model. The urgency of this research is based on the strategic contribution of Islamic boarding schools and the lack of specific regional regulations. A descriptive qualitative method was used to examine the implementation of four main strategies. The results show that the Perda formulation process was participatory, transparent, and accountable. This was realized through: (1) Informative Strategy (transparency through official and local media); (2) Consultative Strategy (structured formal consultations such as FGDs and Public Hearings); (3) Deliberative Strategy (the Regional People's Representative Council (DPRD) acts as a neutral facilitator ensuring equal positions in dialogue); and (4) Collaborative Strategy (creating synergy through structured feedback loops, capacity building, and field verification). The comprehensive implementation of these four strategies ensures that the resulting Perda has substantial legitimacy because it is the product of a co-creation process that fully involves the Islamic boarding school community as the main stakeholder.